Acute cerebral venous outflow obstruction during convexity meningioma resection. (10th December 2021) - Shen, Bo; Hu, Changchen; Jia, Liming; Hu, Yanjun
Abstract: Background: Cerebral venous outflow obstruction involves idiopathic intracranial hypertension, and the most common related condition is dural venous sinus stenosis or, in other words, an obstruction of the dural venous sinuses. In these cases, the pathological process is often chronic, displays only mild symptoms, and rarely requires urgent surgical intervention. In this study, we present a unique case involving an acute cerebral venous outflow obstruction that occurred during meningioma resection that ultimately had catastrophic consequences. Materials and methods: The patient's preoperative imaging only revealed an unremarkable frontal convexity meningioma with an average diameter exceeding 8 cm. She was admitted for a scheduled right frontoparietal craniotomy for lesion resection. Results: The patient's unique congenital dural venous sinus structure along with a non-surgical epidural hematoma both contributed to a catastrophic outcome, causing a progressive hemispheric encephalocele, significant blood loss, and wound closure difficulties. Conclusion: Neurosurgeons should place an additional focus on cerebral venous outflow patency during tumor resection, even if the tumor does not involve the transverse or sigmoid sinuses. It is well known that the tacking sutures play an essential role in preventing an epidural hematoma, but the procedure to mitigate hematomas occurring outside the surgical field of view is not fully recognized by neurosurgeons. If dural tacking sutures are placed after complete tumor resection, the prophylactic effect for preventing EDH in the non-surgical areas may not be guaranteed. Therefore, we strongly advocate for the tacking sutures to be accurately placed before dural incisions are made.